Quality of Research in Graduate Schools of Ugandan Universities: An Authoritative Opinion - Lwanga Bukenya, Aloysius (Student's Journal of Health Research Africa, 2022)
This paper is based on analyzed literature on the appraisal of the quality of research and innovations in Ugandan universities. Its purpose is to reflect on the factors that impact Uganda’s ranking globally. It focuses on graduate schools where the component of research and innovation is a requirement in many programs of study. The paper is partly an appraisal of the performances of university education that revolves around the traditional functions: teaching-learning, carrying out research, and engagement in community outreach services. It attempts to articulate major challenges which Ugandan graduate students face and to propose some strategies for a way forward.
Keywords: Graduate school; Graduate students; Quality research; Innovations; Community outreach